DOI: 10.35537/10915/4603
|View full text |Cite
|
Sign up to set email alerts
|

Equinodermos del Paleozoico superior de la cuenca de Tepuel-Genoa

Abstract: El objetivo inicial de esta tesis fue el conocimiento de la fauna de equinodermos de la cuenca de Tepuel-Genoa del Paleozoico superior con fines bioestratigráficos y paleogeográficos. Durante el desarrollo de la misma me topé con el escaso conocimiento que existe de este grupo fósil para la Argentina, no solo en lo que hace a la descripción sistemática de los mismos en donde la mayoría de las citas corresponde a equinoideos del Cenozoico, sino a la falta de textos en habla hispana que traten los diferentes asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Page et al (1984) considered the Río Genoa Formation as a lateral equivalent of the middle and upper parts of the Mojón de Hierro Formation. Furthermore, Andreis and Cúneo (1989) and Hlebszevitsch and Sabattini (2005) have suggested that both formations are at least partially equivalent. Taboada and Pagani (2010) described two new faunal associations and proposed that the Río Genoa Formation mostly overlay the Mojón de Hierro Formation, but with possible minor lateral interfingering between the uppermost part of the Mojón de Hierro Formation and the lowermost part of the Río Genoa Formation (Fig.…”
Section: Geological and Stratigraphic Setting And Key Biota Contentmentioning
confidence: 99%
See 4 more Smart Citations
“…Page et al (1984) considered the Río Genoa Formation as a lateral equivalent of the middle and upper parts of the Mojón de Hierro Formation. Furthermore, Andreis and Cúneo (1989) and Hlebszevitsch and Sabattini (2005) have suggested that both formations are at least partially equivalent. Taboada and Pagani (2010) described two new faunal associations and proposed that the Río Genoa Formation mostly overlay the Mojón de Hierro Formation, but with possible minor lateral interfingering between the uppermost part of the Mojón de Hierro Formation and the lowermost part of the Río Genoa Formation (Fig.…”
Section: Geological and Stratigraphic Setting And Key Biota Contentmentioning
confidence: 99%
“…Scale bar 5 mm. 27-39, Bivalvia association from Pampa de Tepuel Formation, at 1100 m. from the base (FT1-13 Bed, Freytes, 1971) 1992; Hlebszevitsch and Sabattini, 2005); brachiopods (Simanauskas, 1991;Taboada and Pagani, 2010); bivalves (González, 1974(González, , 2006Pagani, 2004aPagani, ,b, 2005Pagani, , 2006a and hyolithids (Pagani and Sabattini, 1999). For a list of the species registered in this area see Appendix A, localities 9 and 10; selected specimens also illustrated in Fig.…”
Section: At Puesto La Carlota Region (Fig 2)mentioning
confidence: 99%
See 3 more Smart Citations